The Evolution of Selfing Is Accompanied by Reduced Efficacy of Selection and Purging of Deleterious Mutations. Issue 3 (30th December 2014) - Arunkumar, Ramesh; Ness, Rob W; Wright, Stephen I; Barrett, Spencer C H
Abstract: The transition from outcrossing to selfing is predicted to reduce the genome-wide efficacy of selection because of the lower effective population size ( N e ) that accompanies this change in mating system. However, strongly recessive deleterious mutations exposed in the homozygous backgrounds of selfers should be under strong purifying selection. Here, we examine estimates of the distribution of fitness effects (DFE) and changes in the magnitude of effective selection coefficients ( N e s ) acting on mutations during the transition from outcrossing to selfing. Using forward simulations, we investigated the ability of a DFE inference approach to detect the joint influence of mating system and the dominance of deleterious mutations on selection efficacy. We investigated predictions from our simulations in the annual plant Eichhornia paniculata, in which selfing has evolved from outcrossing on multiple occasions. We used range-wide sampling to generate population genomic datasets and identified nonsynonymous and synonymous polymorphisms segregating in outcrossing and selfing populations. We found that the transition to selfing was accompanied by a change in the DFE, with a larger fraction of effectively neutral sites ( N e s < 1), a result consistent with the effects of reduced N e in selfers. Moreover, an increased proportion of sites in selfers were under strong purifying selection ( N e s > 100), and simulations suggest that this is due to the exposure of recessive deleterious mutations. We conclude that the transition to selfing has been accompanied by the genome-wide influences of reduced N e and strong purifying selection against deleterious recessive mutations, an example of purging at the molecular level.